PENINGKATAN GERAKAN MASYARAKAT HIDUP SEHAT MELALUI PELATIHAN SANTRI POSKESTREN DI PESANTREN RIYADUL ULUM WADDA’WAH KOTA TASIKMALAYA - Asep Riyana; Arip Rahman (Jurnal Pengabdian Masyarakat DEDIKASI, 2024)
The Healthy Living Community Movement (GERMAS) is a systematic and planned action carried out jointly by all components of the nation with awareness, willingness and ability to behave healthily to improve the quality of life. The implementation of GERMAS must start from the family, because the family is the smallest part of society that forms personality. GERMAS can be done by: Doing physical activity, consuming vegetables and fruit, not smoking, not consuming alcohol, checking your health regularly, cleaning the environment, and using a toilet. In the initial stage, GERMAS nationally started by focusing on three activities, namely: 1) Carrying out 30 minutes of physical activity per day, 2) Consuming fruit and vegetables; and 3) Check your health regularly. GERMAS is a national movement initiated by the President of the Republic of Indonesia which prioritizes promotive and preventive efforts, without neglecting curative-rehabilitative efforts by involving all components of the nation in promoting the healthy paradigm. To make GERMAS a success, you cannot only rely on the role of the health sector alone. The aim of this community service activity is to socialize the program that has been created by the government so that good habits can be achieved in society with healthy community living habits. Based on a preliminary study at the Cibeureum health center, it turns out that this program has not been socialized either to Cibeureum health center staff or to the community. So we feel the need to socialize GERMAS to help government programs achieve optimal improvement in public health, especially at the Riyadul Ulum Wadda'wah Islamic Boarding School, Tasikmalaya City. community (IbM) Tasikmalaya Health Polytechnic. Activities were carried out over a period of 1 year